Evaluación de riesgos de control sobre los procedimientos administrativos y financieros de la empresa pública TRANSVIAL EP de la ciudad de Babahoyo - Fernández Santillán, José Guillermo (2020)
The research carried out in the Public Company Transvial EP allows determining problems in the development of administrative procedures, compliance with internal regulatory bases and effects on financial activities, which is why the objective of the case study lies in the analysis of how processes are executed of administration and finances with respect to the income received by concept of rental of commercial premises of the Terrestrial Terminal and vehicle registration. The applied methodology is made up of the types of exploratory and field research, the inductive method is also applied where particular problematic situations are analyzed. The technique applied to collect information from the observation units is a structured interview using an internal control questionnaire. The results obtained in the investigative process lie in the weak compliance with regulations and inadequate control to monitor the competences of public collaborators, where the applied technique allows us to interpret that the revenue control process and internal procedures of the Collection department have a level of low confidence and moderate risk of control, however, the company is not affected in the income they receive due to meeting its general budget.